Pelatihan Pembuatan Puding Sedot Temulawak sebagai Peningkat Imun Anak di Masa Pandemi - Idham, Hanafi; Chaidir, Kholid; Islah, Andari Putri (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Corona virus outbreak that attacks the respiratory tract, one of the causes is a decrease in the body's immune system. Decreased immune system with the same symptoms in people infected with the Corona virus including cough, flu, fever and shortness of breath. Providing balanced nutrition is very important for children, as a prevention effort. Increasing the body's immune system can be done by consuming drinks from spices, one of which is Temulawak. Community service is carried out by providing training on 25 to housewives (PKK) and carried out in December 2020 - January 2021 in the Sukorame Village, Pekanbaru City. The method used is counseling and demonstration of making Temulawak suction pudding (pudot) while still paying attention to health protocols. Residents who participated in this training experienced an increase in knowledge and skills. It was found that 84% of the residents were skilled in making Pudot Temulawak.